Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0070755
|View full text |Cite|
|
Sign up to set email alerts
|

Establishment of a Novel Murine Model of Ischemic Cardiomyopathy with Multiple Diffuse Coronary Lesions

Abstract: ObjectivesAtherosclerotic lesions of the coronary arteries are the pathological basis for myocardial infarction and ischemic cardiomyopathy. Progression of heart failure after myocardial infarction is associated with cardiac remodeling, which has been studied by means of coronary ligation in mice. However, this ligation model requires excellent techniques. Recently, a new murine model, HypoE mouse was reported to exhibit atherogenic Paigen diet-induced coronary atherosclerosis and myocardial infarction; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…The same inconvenient of large involvement of the heart structures and even of the whole organism is obvious when lesions are caused by injection of drugs [17,18,23]. Ferric chloride use is not compatible with MRI imaging investigation, necessary to determine the lesion extent and evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same inconvenient of large involvement of the heart structures and even of the whole organism is obvious when lesions are caused by injection of drugs [17,18,23]. Ferric chloride use is not compatible with MRI imaging investigation, necessary to determine the lesion extent and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Heart main artery obstruction was obtained by physical means: cold or heat injury, radiofrequencies [14,15], chemical methods: injections or application of chemicals on the myocardium [16][17][18] or surgical ones as vessel ligation [19]. Presently the most usual experimental model of creating a cardiac lesion remains the temporary or permanent ligation of a coronary artery [9][10][11][12][19][20][21][22] or other type of heart vessels occlusion [23]. The advantage of this model is its proximity with the injury caused by myocardial infarction in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using SR-BI KO/ApoeR61 h/h mice (mixed C57BL/6 6 129 background) Nakaoka et al [68] established a novel murine model called as “modified HypoE mouse” of ischemic cardiomyopathy with multiple diffuse coronary lesions. They shortened the sustained Paigen diet for the HypoE mice causing mice to survive longer.…”
Section: Mouse Models In Cardiac Researchmentioning
confidence: 99%
“…In contrast, hypomorphic E mice deficient in SR-B1 with low expression of an allelic variant of mouse apoE (SR-B1 −/− /ApoeR61 h/h ), have a normal life span on a normal chow diet, but die prematurely from repeated spontaneous myocardial infarction as a result of atherothrombosis after 4–8 weeks on a Paigen diet 8 . Recently, some of us showed that by reducing Paigen diet exposure to 1 week extended survival of SR-B1 −/− /ApoER61 h/h mice, and induced a state of progressive ischemic cardiomyopathy 9 .…”
Section: Introductionmentioning
confidence: 99%